The place of a socio-cultural environment in climate change discourse - Charles W. Recha (Geography Notebooks, 2020)
The significance of climate change is reflected in global level efforts such as Conference of Parties and Intergovernmental Panel on Climate Change reporting. The global level platform develops consensus on evidences and pathways to climate change mitigation and adaptation. Unfortunately, these efforts often lack social-cultural dynamics to climate change. This study adopted a desktop survey to establish the place of socio-cultural dynamics in climate change discourse. In this study, it is argued that socio-economic security and attributes, cultural-orientation and inter-group dimensions are key determinants to implementation of climate change programmes. To successfully design and implement climate change mitigation and adaptation strategies, first address socioeconomic securities of communities, bring on board sub-national considerations and package climate change impacts as a threat to nationalism.